Sources Of Larval Identities For Amphibians Of India - Das, I.; Dutta, S. (Hamadryad, 2007)
The systematic status of knowledge of larvae of amphibians occurring within the political limits of India is reviewed. Each description is ranked in order of completeness and the presence or absence of images. Of the 265 species of amphibians (representing three orders– Anura, Gymnophiona and Caudata), 118 have known tadpole stages. This represents 44.5% of the total fauna, significantly lower than those of at least two regional faunas.